Inteligencia emocional y comprensión lectora en alumnos de sexto grado de primaria de la Red N° 4 distrito del Callao - Castellano Díaz, Jesús Estela (2010)
In this research, is intended to determine the relationship between emotional intelligence and reading comprehension in 6th grade of Primary Schools of Red Nº 4 of Callao District students. The sampling was applied by conglomerates bietápico; the sample was made up of 155 students of both genders. The instruments used were the inventory of BarOn ICE: NA Emotional Intelligence in children and adolescents (short form) and Reading Comprehension Linguistics complexity 6 test form A; there are instruments that have validity and reliability in our country. The results were: there is weak relationship between emotional intelligence and reading comprehension. There is no relationship between interpersonal and intrapersonal intelligence with reading comprehension. However if there is a significant relationship between adaptability, handling stress with reading comprehension.